Rewitalizacja jako podstawa rozwoju obszarów problemowych w miastach - Ziółkowski, Marek; Górniak, Remigiusz (Revitalization as the Basis of Urban Problem Areas, 2007)
The general aim of the paper is presenting the idea of revitalization in relation to the concept of particular revitalization programme. The key aspect of the paper is presenting the author's approach towards the problem - implementing and managing of revitalization programme in degraded areas facing the problem of social and economic exclusion. The paper is divided into three parts. The first-defining and describing categories of problem areas in the cities, the second - explaining the terra of revitalization, the last including the proposed methods.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1161, s. 300-309